Deployable designs to temporarily convert subacute hospital rooms into palliative care rooms - Khine, Thinn Thinn; Workman, Barbara; Pan, Hanmei; Aung, Nyein Chan (Australasian journal on ageing, 2021)
Objective To explore the design of deployable articles that can turn subacute hospital rooms into palliative care rooms to provide better patient‐centred care and to meet the shortage of dedicated palliative care spaces in Australia. Methods Clinicians and a design researcher collaborated to review the literature, obtain clinical/practitioner feedback on needs and use design research methods to produce design concepts and prototypes for use in the subacute care hospital setting. Results A design solution that included: (a) A guest‐bed module for improved family togetherness and room personalisation; and (b) A digital connectivity module designed to provide family togetherness virtually. Conclusions Informed design solutions for palliative care spaces were derived from clinical feedback and literature evidence. Clinicians expressed great interest and support for further development and implementation in Victorian hospitals. This exploratory concept also provides insights for future research and innovation in the design of palliative care environments.